Age‐dependent effects of the p75 neurotrophin receptor modulator LM11A‐31 on Alzheimer's disease biomarkers in a 26‐week safety and exploratory endpoint trial. (20th December 2022) - Shanks, Hayley R. C.; Börjesson‐Hanson, Anne; Windisch, Manfred; Massa, Stephen M.; Longo, Frank M.; Schmitz, Taylor W.
Abstract: Background: The p75 neurotrophin receptor (p75NTR) modulates pro‐ and anti‐apoptotic pathways as well as neurite and neuritic spine integrity. This receptor is expressed in cells vulnerable to aging and disease, including basal forebrain cholinergic neurons and hippocampal pyramidal neurons. It is also expressed by glial cells under pathological conditions. Pharmacological modulation of the p75NTR with LM11A‐31 alters both age‐ and disease‐related neuronal dysfunction. For example, LM11A‐31 reverses neuritic pathology in aged mice and reduces amyloid‐induced tau phosphorylation in mouse models of Alzheimer's disease (AD). In this proof‐of‐concept study, we examined the effects of LM11A‐31 treatment on longitudinal neuroimaging and CSF biomarkers in humans with mild to moderate Alzheimer's disease. Based on our preclinical work, we hypothesized that age and disease may interact to predict response to LM11A‐31 treatment in humans. Therefore, we additionally conducted subgroup analyses of drug effect in older and younger individuals. Method: Participants with mild to moderate AD (MMSE score = 18‐26; age 55‐85 years) were enrolled in a 26‐week placebo‐controlled phase 2a safety and exploratory endpoint trial of LM11A‐31. Exploratory outcome measures included structural MRI, CSF AD core biomarkers, and CSF biomarkers related to pathological processes affected in mouse studies including synaptic integrity and inflammation. For placebo and drug, age subgroups were defined using a median‐split: younger (<72 years) and older (> = 72 years). Result: Whole brain structural MRI analyses revealed that 26‐week treatment with LM11A‐31 reduced longitudinal grey matter degeneration in AD‐vulnerable brain regions including the inferior temporal gyrus, insula, frontal operculum and retrosplenial cortex. Furthermore, drug treatment, compared to placebo, prevented longitudinal increases of CSF tau, the presynaptic biomarker SNAP25, and the inflammatory biomarker YKL‐40. Median split analyses demonstrated that drug effects for structural MRI and CSF measures were consistently stronger in younger individuals. Conclusion: This investigation highlights that biomarkers may demonstrate age‐dependency in response to therapeutic interventions in the context of mild‐moderate AD. Our results may inform biomarker selection and design of future studies of LM11A‐31 in human AD.